Psychometric validation of the Portuguese version of the Measure of Anxiety in Selection Interviews - Santos, A. C.; Arriaga, P.; Simões, C. (International Journal of Selection and Assessment, 2021)
Feeling anxiety in a job interview is common. It is important to have a valid, reliable, and culturally adapted measure, enabling cross-cultural comparisons. Our main goal was to examine the psychometric properties of the Measure of Anxiety in Selection Interviews (MASI) in a Portuguese sample since no similar measure is available in the Portuguese language. The MASI was developed to capture five dimensions of anxiety: Communication, appearance, social, performance, and behavior. We tested 436 participants (337 women; aged 18–61 years old) with and without prior job interview experience. Confirmatory factor analysis indicated an adequate fit for the five-factor solution. Good internal and test-retest reliability (two weeks between assessments) was observed. The MASI-P positively correlated with social anxiety/fear, but negatively correlated with age, number of previous job interviews, and perceived performance on the last job interview. Overall, the use of MASI-P can be advantageous in job interview training, research, and employment processes.